Enrollment and attendance to Cardiac Rehabilitation after Percutaneous Coronary Intervention in Sarawak : A Prospective Study - Chai, Li Sze; Sidiah, John Siop; Lily, Lim (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
Abstract: Background: Cardiac rehabilitation is vital for cardiac patients, especially after the percutaneous coronary intervention as it is proven to reduce recurrent cardiac event and death. The ongoing CR participations of the patients in Sarawak after percutaneous coronary intervention have not been explored. Purpose: To examine the enrollment and attendance to cardiac rehabilitation among patients who have underwent percutaneous coronary intervention in Sarawak. Methods: A prospective study was conducted. Data on baseline characteristics, diagnosis, smoking status, and referrals received for CR were collected for selected subjects prior to hospital discharge. Their attendances to CR programme were followed up at two months after hospital discharge. Independent sample Ttest was used to analyse the continuous data and Chi square test was conducted for categorical data to identify the differences in characteristics between patients who was enrolled for CR and those who was not. Results: Three hundred and eighty patients were recruited in this study. Among these patients, 141 patients (37.11%) were referred to CR. Only 58 patients (15.3%) completed all the eight sessions of the CR programme, 276 patients (72.6%) did not turn up and 46 patients (12.1%) dropped out before completing all the sessions. Patients who were enrolled in CR were more likely to be men (p=0.001), Malay (p=0.000), having travel time of less than 1 hour from home to hospital (p=0.000), and able to drive (p=0.009). Conclusions/ Implications for Practice: The enrollment and attendance rate of CR in Sarawak is low. Men, Malay, staying near to the hospital, and being a driver were more likely to be referred to CR. Further study on this is needed as CR is proven to benefit the patients.